2
$\begingroup$

The fundamental theorem of calculus states:

If $f$ is continuous on $[a,b]$, then if $g(x) = \int_{a}^{x}f(t)\,dt,~ \textrm{then}~g'(x) = f(x)$.

In Example 4, the chain rule is used because the upper bound, $x^4$ needed to be differentiated. My question is, why is that and where is that implied given the theorem stated above? enter image description here

Similarly, find $h'(x)$ of $h(x) = \int_{1}^{e^x} \ln(t)\,dt$ The answer is $h'(x) = xe^x$, which seems to be in line with Example 4. Per previous examples in the book, one might expect the answer to be $h'(x) = \ln(e^x)$ though.

$\endgroup$
1
$\begingroup$

With $u := e^x$ the derivative becomes $$\frac{d}{du} \int_1^u \ln(t) dt \frac{du}{dx} = \ln(u) \frac{du}{dx} = \ln(e^x) \frac{d e^x}{dx} = x \cdot e^x.$$

$\endgroup$
3
$\begingroup$

If $g(x) = \int_{a}^{x}f(t)dt$, then, by the chain rule, $$\frac{d}{dx}(g(h(x)))=g'(h(x))\cdot h'(x)=f(h(x))\cdot h'(x)$$ where, at the second step, by the FTC, $g'(h(x))=\left(\frac{d}{dy}\left(\int_{a}^{y}f(t)dt\right)\right)_{y=h(x)}=f(h(x))$.

So, as regards your example with $f(x)=\ln(x)$, $a=1$ and $h(x)=e^x$, we have that $$\frac{d}{dx}\left( \int_{1}^{e^x} \ln(t)\,dt\right)=\ln(e^x)\cdot (e^x)'=x\cdot e^x.$$ P.S. Note that $$\int_{1}^{e^x} \ln(t)\,dt=\left[\ln(t)t-t\right]_1^{e^x}=xe^x-e^x+1$$ and it is easy to check that $\frac{d}{dx}\left( xe^x-e^x+1\right)=xe^x$.

$\endgroup$
  • $\begingroup$ My confusion is comings from WHY you have to use the chain rule, rather then how the chain rule is used in this problem $\endgroup$ – Evan Kim Feb 7 at 16:30
  • $\begingroup$ We have to use the chain rule because we have to differentiate a composition of two functions, $g(h(x))$. The FTC tells use how to compute the derivative of $g$. $\endgroup$ – Robert Z Feb 7 at 16:36
2
$\begingroup$

In contrast with the other answers, you could use the other form of the fundamental theorem of calculus which states that (under suitable conditions) if $F'(t) = f(t)$ then $\displaystyle \int_a^b f(t) \, dt = F(b) - F(a).$ With $f(t) = \ln t$ you can take $F(t) = t \ln t - t$ so that $$h(x) = \int_1^{e^x} \ln t \, dt = (e^x \ln(e^x) - e^x) - (0 - 1) = x e^x - e^x + 1$$ and $$h'(x) = xe^x + e^x - e^x = xe^x.$$

$\endgroup$
2
$\begingroup$

Do a concrete example to get a feel first: $$ \begin{align} \frac{d}{dx}\left(h(x)\right) &=\frac{d}{dx}\left(\int_{1}^{e^x}\ln{t}\,dt\right)\\ &=\frac{d}{dx}\left(\left[t\ln{t}-t\right]_{1}^{e^x}\right)\\ &=\frac{d}{dx}\left(\left[e^x\ln{e^x}-e^x-(e\ln{1}-1)\right]\right)\\ &=\frac{d}{dx}\left(xe^x-e^x+1\right)\\ &=\frac{d}{dx}(xe^x)-\frac{d}{dx}(e^x)+\frac{d}{dx}(1)\\ &=e^x+xe^x-e^x+0\\ &=xe^x. \end{align} $$

Then do another one, but this time for a general case:

$$ \begin{align} \frac{d}{dx}\left(\int_{a}^{u(x)}f(t)\,dt\right) &=\frac{d}{dx}\left(\left[F(t)\right]_{a}^{u(x)}\right)\\ &=\frac{d}{dx}\left(F(u(x))-F(a)\right)\\ &=\frac{d}{dx}\left(F(u(x))\right)-\frac{d}{dx}(F(a))\\ &=F'(u(x))-0\\ &=F'(u)\cdot u'(x)\\ &=f(u)\cdot u'(x)\\ &=f(u)\cdot\frac{du}{dx} \end{align} $$

Where $F'(x)=f(x)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.